Operando Study of the Active Phase in Liquid GaPt Alloy Catalysts - Moritz, Michael; Wichmann, Christoph; Steinmetz, Marius; Steinrück, Hans-Peter; Papp, Christian (Small Science, 2025)
The operando study investigates propane dehydrogenation (PDH) using a liquid gallium-platinum catalyst based on the supported catalytically active liquid metal solutions (SCALMS) concept. The focus is on monitoring and analyzing the active phase during reaction using near-ambient pressure X-ray photoelectron spectroscopy (NAPXPS) combined with gas phase analysis. This approach proves practical in tracking surface changes and chemical states during catalytic reactions, providing real-time insights into the catalyst behavior. PDH, an industrially significant reaction, is investigated using a GaPt SCALMS with 1 at.% Pt content. The findings reveal that metallic liquid GaPt SCALMS exhibit high activity, while the presence of oxygen in the feed stream significantly lowers the activity of the catalyst. While current liquid metal catalysts often experience an activation period, a pathway to achieving stable conversion rates right after the start is demonstrated. This stability lays a foundation for developing next-generation catalysts with improved performance. The investigation also highlights the critical influence of oxidic Ga on catalytic activity, offering valuable guidance for optimizing catalyst design. Overall, the findings underscore the practical importance of NAPXPS in advancing the understanding of surface properties in catalytic systems.
CRIS-Team Scopus Importer:2025-12-12
Keywords: active site; catalysis; dehydrogenation; liquid metals; near-ambient pressure X-ray photoelectron spectroscopy; operando; quadrupole mass spectrometry